Positive electrode slurry, positive electrode sheet and electrochemical device containing the same
By using a composite dispersant of acidic and alkaline dispersants in the positive electrode slurry of lithium iron phosphate and polyvinylidene fluoride in the lithium-ion battery, the dispersants in the prior art are solved by combining carbon-coated lithium iron phosphate and polyvinylidene fluoride. The problem of junction performance achieves battery performance with high peeling force and excellent capacity retention.
Patent Information
- Application Number
- CN202411377358.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-30
AI Technical Summary
In the positive electrode slurry of existing lithium-ion batteries, dispersants cannot improve the coating performance and bonding performance at the same time, resulting in insufficient discharge capacity and reliability of the battery.
Using a composite dispersant including an acidic dispersant and an alkaline dispersant, the mass ratio of components A and B is adjusted, and the carbon-coated lithium iron phosphate and polyvinylidene fluoride are combined to form excellent coating and bonding. performance.
The high peeling force of the positive electrode sheet and the excellent capacity retention rate of the electrochemical device are achieved, and the cycle stability and consistency of the lithium-ion battery are improved.
Smart Images

Figure CN118888759B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a positive electrode slurry, a positive electrode sheet and an electrochemical device containing the same. Background Art
[0002] In the positive electrode slurry used in lithium-ion batteries, the particles of active materials often have a certain size and aggregation state. If the particles aggregate together, the specific surface area of the positive electrode material will be reduced, limiting the insertion and extraction rate of lithium ions, thereby reducing the discharge capacity of the battery. Therefore, in order to improve the dispersibility of the positive electrode material, a dispersant needs to be added. The addition of a dispersant can not only improve the dispersibility of the slurry, but also reduce the viscosity of the slurry and improve its fluidity. Appropriate viscosity helps the uniform distribution and coating performance of the positive electrode slurry during the coating process, thereby improving the consistency and reliability of battery manufacturing. However, the dispersant in the prior art cannot ensure the bonding performance of the positive electrode slurry while improving the coating performance. Summary of the invention
[0003] In order to ensure that the positive electrode slurry has both excellent coating performance and bonding performance, the present invention provides a positive electrode slurry, a positive electrode sheet and an electrochemical device containing the same. The positive electrode slurry uses a composite dispersant including two different components, and has good coating performance and excellent bonding performance. The positive electrode sheet prepared by using the positive electrode slurry has a high peeling force, and the obtained electrochemical device (especially a lithium ion battery) has an excellent capacity retention rate.
[0004] To achieve the above objectives, the present invention adopts the following technical solutions.
[0005] In a first aspect, the present invention provides a positive electrode slurry, which includes a positive electrode active material, a binder and a dispersant; wherein the dispersant includes component A and component B; component A is an acidic dispersant; component B is an alkaline dispersant; the mass ratio of component A to component B is (1-30): 1; the positive electrode active material includes carbon-coated lithium iron phosphate; and the binder includes polyvinylidene fluoride.
[0006] In a second aspect, the present invention provides a positive electrode sheet, comprising a positive electrode current collector and a positive electrode material layer located on at least one surface of the positive electrode current collector, wherein the positive electrode material layer is formed by the positive electrode slurry as described above.
[0007] In a third aspect, the present invention provides a positive electrode sheet, comprising a positive electrode current collector and a positive electrode material layer located on at least one surface of the positive electrode current collector, wherein the positive electrode material layer comprises a positive electrode active material, a binder and a dispersant; the dispersant comprises component A and component B; component A is an acidic dispersant; component B is an alkaline dispersant; the mass ratio of component A to component B is (1-30): 1; the positive electrode active material comprises carbon-coated lithium iron phosphate; the binder comprises polyvinylidene fluoride.
[0008] In a fourth aspect, the present invention provides an electrochemical device comprising the positive electrode sheet as described above.
[0009] The positive and progressive effects of the present invention are:
[0010] The present invention provides a positive electrode slurry, which uses a composite dispersant including a component A and a component B with different acidity and alkalinity, achieving both excellent coating performance and excellent bonding performance. The positive electrode sheet prepared by using the positive electrode slurry has high peeling force, good consistency and reliability, and the electrochemical device (especially lithium ion battery) prepared further has good cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 Graph showing the change in viscosity of the positive electrode slurry with standing time in Example 1 and Comparative Examples 1-2. DETAILED DESCRIPTION
[0012] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0013] Cathode slurry
[0014] In the positive electrode slurry provided in the first aspect of the present invention, it includes a positive electrode active material, a binder and a dispersant; the dispersant includes component A and component B; the component A is an acidic dispersant; the component B is an alkaline dispersant; the mass ratio of the component A to the component B is (1-30): 1; the positive electrode active material includes carbon-coated lithium iron phosphate; the binder includes polyvinylidene fluoride.
[0015] Dispersants
[0016] In the present invention, the component A may be an acidic dispersant commonly used in the art.
[0017] In the present invention, the acidic dispersant may include one or more of a phosphoric acid dispersant, a carboxylic acid dispersant, an olefinic acid dispersant and a phenolic dispersant.
[0018] The phosphoric acid dispersant refers to a dispersant containing phosphoric acid or a phosphate group. For example, the phosphoric acid dispersant can be selected from one or more of trialkyl phosphate, stearic acid phosphate, heterocyclic phosphate, catechol diphosphate and pyridinium phosphate.
[0019] The carboxylic acid dispersant refers to a dispersant containing a carboxylic acid or a carboxylate group. For example, the carboxylic acid dispersant can be selected from one or both of carboxylic acid polyester and maleic acid.
[0020] The olefinic acid dispersant refers to a dispersant containing olefinic acid or olefinic acid ester groups. For example, the olefinic acid dispersant can be selected from one or two of polyacrylate, polyacrylic acid, methacrylic acid and acrylic acid.
[0021] The phenolic dispersant refers to a dispersant containing a phenolic hydroxyl group, such as sorbitan monolaurate.
[0022] In some preferred embodiments, the component A includes a phosphoric acid-based dispersant.
[0023] In some optional embodiments, the component A includes a phosphoric acid dispersant and a carboxylic acid dispersant.
[0024] In some preferred embodiments, the component A includes one or more of trialkyl phosphates, stearic acid phosphates, heterocyclic phosphates, catechol diphosphates, pyridinium phosphates, carboxylic acid polyesters, maleic acid, polyacrylates, polyacrylic acid, methacrylic acid, acrylic acid and sorbitan monolaurate.
[0025] In some specific embodiments, the component A is one or more of trialkyl phosphate, carboxylic acid polyester, polyacrylic acid and sorbitan monolaurate.
[0026] In a specific embodiment, the component A is trialkyl phosphate and carboxylic acid polyester, and the mass ratio of the trialkyl phosphate to the carboxylic acid polyester is preferably 1:1.
[0027] In the present invention, the component B may be a basic dispersant commonly used in the art.
[0028] In the present invention, the alkaline dispersant may include one or more of an amine dispersant, an ammonia dispersant, an ammonium dispersant, a heterocyclic dispersant, an amide dispersant and a cyano dispersant.
[0029] The amine dispersant may be selected from one or more of polyethyleneimine, triethanolamine, tripropanolamine, polyetheramine and polyetheramine methyl ether.
[0030] The ammonium dispersant is, for example, cetyltrimethylammonium bromide (CTAB).
[0031] The heterocyclic dispersant may be selected from one or more of pyrrole dispersants, pyridine dispersants, furan dispersants and imidazole dispersants. The pyrrole dispersant may be selected from one or more of pyrrole, polypyrrole, indole and 4-pyrrolidone.
[0032] Wherein, the amide dispersant can be selected from one or more of polyvinyl pyrrolidone (PVP) and benzamide.
[0033] The cyano dispersant may be selected from one or more of polyacrylonitrile, polycyanate and cyano-tert-butyloxypropyltrimethoxysilane.
[0034] In some preferred embodiments, the component B includes one or more of polyethyleneimine, triethanolamine, tripropanolamine, polyetheramine, polyetheramine methyl ether, hexadecyltrimethylammonium bromide, pyrrole, polypyrrole, 4-pyrrolidone, indole, polyvinylpyrrolidone, benzamide, polyacrylonitrile, polycyanate and cyano-tert-butyloxypropyltrimethoxysilane.
[0035] In some specific embodiments, the component B is one or more of polyvinyl pyrrolidone, hexadecyltrimethylammonium bromide, polyacrylonitrile and benzamide.
[0036] In some preferred embodiments, the dispersant includes trialkyl phosphate and polyvinyl pyrrolidone.
[0037] In some preferred embodiments, the dispersant includes carboxylic acid polyesters, trialkyl phosphates, and polyvinyl pyrrolidone.
[0038] In some preferred embodiments, the dispersant includes a carboxylic acid polyester and polyvinyl pyrrolidone.
[0039] In some preferred embodiments, the dispersant includes polyacrylic acid and polyvinyl pyrrolidone.
[0040] In some preferred embodiments, the dispersant includes sorbitan monolaurate and polyvinylpyrrolidone.
[0041] In some preferred embodiments, the dispersant includes trialkyl phosphates and benzamides.
[0042] In some preferred embodiments, the dispersant includes trialkyl phosphates and cetyltrimethylammonium bromide.
[0043] In some preferred embodiments, the dispersant includes trialkyl phosphate and polyacrylonitrile.
[0044] In some optional embodiments, the content of component A is 0.005%-1.5%, preferably 0.01%-1%, for example, 0.01%, 0.05%, 0.1%, 0.12%, 0.2% or 1%, where the percentage is the mass of component A as a percentage of the total mass of the components in the positive electrode slurry excluding the solvent.
[0045] In some optional embodiments, the content of component B is 0.005%-1%, preferably 0.01%-1%, for example 0.01%, 0.03%, 0.05% or 0.15%, where the percentage is the mass of component B to the total mass of the components in the positive electrode slurry excluding the solvent.
[0046] In some optional embodiments, the content of the dispersant is 0.03%-2%, for example, 0.055%, 0.06%, 0.10%, 0.105%, 0.11%, 0.13%, 0.15%, 0.25%, 1.05%, 1.55%, where the percentage is the mass of the dispersant as a percentage of the total mass of the components in the positive electrode slurry excluding the solvent.
[0047] In some optional embodiments, the mass ratio of component A to component B is (1-30):1, for example, 2:1, 3.3:1, 4:1, 10:1 or 20:1.
[0048] Positive electrode active material
[0049] In the present invention, the lithium iron phosphate in the carbon-coated lithium iron phosphate can be a conventional lithium iron phosphate positive electrode active material in the art, which is generally LiFePO4 (LFP), but is not limited to LiFePO4, and can also be doped with other metal elements, the metal elements include one or more of Zr, Mg, Mn, Al, Ti, Zn, Cr, Ni, Co and Nb, and the doping amount of the metal element can be 0.1%-10%, and the percentage is the percentage of the mass of the metal element to the mass of LFP. Among them, when the metal element is Mn, the lithium iron phosphate in the carbon-coated lithium iron phosphate is lithium manganese iron phosphate.
[0050] In some preferred embodiments, the positive electrode active material is carbon-coated lithium iron phosphate, wherein the carbon coating amount is generally 0.05%-5%, preferably 0.5%-5%, for example 1.3% or 0.7%, where the percentage is the mass percentage of carbon to the mass percentage of carbon-coated lithium iron phosphate.
[0051] In some optional embodiments, the content of the positive electrode active material is 85%-98%, for example, 95.95%, 96.45%, 96.75%, 97.25%, 97.35%, 97.37%, 97.39%, 97.395%, 97.4%, 97.44%, 97.445% or 98.05%, where the percentage is the mass of the positive electrode active material as a percentage of the total mass of the components in the positive electrode slurry excluding the solvent.
[0052] Binder
[0053] In the present invention, the positive electrode slurry must contain a binder, and the binder includes polyvinylidene fluoride (PVDF).
[0054] In some optional embodiments, the content of the binder is 0.5%-10%, preferably 1%-10%, for example 0.9% or 1.8%, where the percentage is the mass of the binder to the total mass of the components in the positive electrode slurry excluding the solvent.
[0055] In some optional embodiments, the binder further includes one or more of polytetrafluoroethylene, hexafluoropropylene, polyacrylonitrile, polyimide and perfluorosulfonic acid ionomer.
[0056] In some optional embodiments, the binder further includes one or more of sodium carboxymethyl cellulose, polyolefin, polyacrylic acid (PAA) and polymethyl methacrylate.
[0057] Conductive agent
[0058] In some optional embodiments, the positive electrode slurry further includes a conductive agent.
[0059] The type of the conductive agent is not particularly limited, and is a reagent used to ensure that the electrode has good charge and discharge performance. It can be selected from graphite materials such as natural graphite and artificial graphite, carbon black SP, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black and other carbon black materials, carbon fibers, metal fibers and other conductive fibers, metal powders such as carbon fluoride powder, aluminum powder, nickel powder and other metal powders, zinc oxide, potassium titanate and other conductive whiskers, and titanium dioxide and other conductive metal oxides or polyphenylene derivatives.
[0060] In a specific embodiment, the conductive agent is carbon black SP (SP).
[0061] In some optional embodiments, the content of the conductive agent is 0.2%-3%, for example, 0.7%, where the percentage is the mass of the conductive agent relative to the total mass of the components in the positive electrode slurry excluding the solvent.
[0062] Solvents
[0063] In the present invention, the positive electrode slurry may include a conventional solvent in the art.
[0064] In some optional embodiments, the solvent includes one or more of N-methylpyrrolidone (NMP), dimethyl carbonate, ethylene carbonate, and diethylene carbonate.
[0065] In some optional embodiments, the solid content of the positive electrode slurry is 45%-80%, for example, 62.12%, 62.13%, 63.11%, 63.37%, 63.87%, 64.32%, 64.37%, 64.57%, 64.73%, 64.87%, 65.02%, 65.11%, 65.17%, 65.21%, 65.34%, 65.56%, 65.57%, 65.88%, 67.23% or 67.32%. The solid content refers to the percentage of the total mass of the components other than the solvent in the positive electrode slurry to the mass of the positive electrode slurry.
[0066] In some optional embodiments, the viscosity of the positive electrode slurry is 3000-20000 mPa·s, for example, 4200 mPa·s, 5100 mPa·s, 5200 mPa·s, 5400 mPa·s, 5600 mPa·s, 5700 mPa·s, 5900 mPa·s, 6150 mPa·s, 6200 mPa·s, 6300 mPa·s, 6400 mPa·s, 6700 mPa·s, 6900 mPa·s, 7200 mPa·s or 7300 mPa·s.
[0067] In some optional embodiments, the pH value of the cathode slurry is 4-11, preferably 4-10, for example, 5, 6, 7, 8, 9 or 10.
[0068] In some preferred embodiments, the second mixing time is shorter than the third mixing time.
[0069] In some preferred embodiments, before the first mixing is performed, the components other than the dispersant in the raw material composition of the positive electrode slurry are pre-mixed, and the pre-mixing is performed by stirring.
[0070] In a specific embodiment, the positive electrode slurry includes carbon-coated lithium iron phosphate, polyvinylidene fluoride, carbon black SP, trialkyl phosphate and polyvinyl pyrrolidone, wherein the content of the trialkyl phosphate is 0.1%, and the content of the polyvinyl pyrrolidone is 0.05%.
[0071] In a specific embodiment, the positive electrode slurry includes carbon-coated lithium iron phosphate, polyvinylidene fluoride, carbon black SP, trialkyl phosphate and polyvinyl pyrrolidone, wherein the content of the trialkyl phosphate is 0.1% and the content of the polyvinyl pyrrolidone is 0.03%.
[0072] In a specific embodiment, the positive electrode slurry includes carbon-coated lithium iron phosphate, polyvinylidene fluoride, carbon black SP, carboxylic acid polyester and polyvinyl pyrrolidone, the content of the carboxylic acid polyester is 0.1%, and the content of the polyvinyl pyrrolidone is 0.05%.
[0073] In a specific embodiment, the positive electrode slurry includes carbon-coated lithium iron phosphate, polyvinylidene fluoride, carbon black SP, carboxylic acid polyester, trialkyl phosphate and polyvinyl pyrrolidone, wherein the sum of the contents of carboxylic acid polyester and trialkyl phosphate is 0.1%, and the content of polyvinyl pyrrolidone is 0.05%.
[0074] In a specific embodiment, the positive electrode slurry includes carbon-coated lithium iron phosphate, polyvinylidene fluoride, carbon black SP, polyacrylic acid and polyvinyl pyrrolidone, wherein the content of polyacrylic acid is 0.1% and the content of polyvinyl pyrrolidone is 0.05%.
[0075] In a specific embodiment, the positive electrode slurry includes carbon-coated lithium iron phosphate, polyvinylidene fluoride, carbon black SP, sorbitan monolaurate and polyvinyl pyrrolidone, wherein the content of sorbitan monolaurate is 0.1% and the content of polyvinyl pyrrolidone is 0.05%.
[0076] In a specific embodiment, the positive electrode slurry includes carbon-coated lithium iron phosphate, polyvinylidene fluoride, carbon black SP, trialkyl phosphate and benzamide, wherein the content of the trialkyl phosphate is 0.1%, and the content of the benzamide is 0.05%.
[0077] In a specific embodiment, the positive electrode slurry includes carbon-coated lithium iron phosphate, polyvinylidene fluoride, carbon black SP, trialkyl phosphate and benzamide, wherein the content of the trialkyl phosphate is 0.12%, and the content of the benzamide is 0.03%.
[0078] In a specific embodiment, the positive electrode slurry includes carbon-coated lithium iron phosphate, polyvinylidene fluoride, carbon black SP, trialkyl phosphate and hexadecyltrimethylammonium bromide, wherein the content of trialkyl phosphate is 0.1% and the content of hexadecyltrimethylammonium bromide is 0.05%.
[0079] In a specific embodiment, the positive electrode slurry includes carbon-coated lithium iron phosphate, polyvinylidene fluoride, carbon black SP, trialkyl phosphate and polyacrylonitrile, wherein the content of trialkyl phosphate is 0.1% and the content of polyacrylonitrile is 0.05%.
[0080] In a specific embodiment, the positive electrode slurry includes carbon-coated lithium iron phosphate, polyvinylidene fluoride, carbon black SP, trialkyl phosphate and polyvinyl pyrrolidone, wherein the content of the trialkyl phosphate is 1% and the content of the polyvinyl pyrrolidone is 0.05%.
[0081] In a specific embodiment, the positive electrode slurry includes carbon-coated lithium iron phosphate, polyvinylidene fluoride, carbon black SP, trialkyl phosphate and polyvinyl pyrrolidone, wherein the content of the trialkyl phosphate is 0.05%, and the content of the polyvinyl pyrrolidone is 0.05%.
[0082] In a specific embodiment, the positive electrode slurry includes carbon-coated lithium iron phosphate, polyvinylidene fluoride, carbon black SP, trialkyl phosphate and polyvinyl pyrrolidone, wherein the content of the trialkyl phosphate is 0.2%, and the content of the polyvinyl pyrrolidone is 0.05%.
[0083] In a specific embodiment, the positive electrode slurry includes carbon-coated lithium iron phosphate, polyvinylidene fluoride, carbon black SP, trialkyl phosphate and polyvinyl pyrrolidone, wherein the content of the trialkyl phosphate is 1.5%, and the content of the polyvinyl pyrrolidone is 0.05%.
[0084] In a specific embodiment, the positive electrode slurry includes carbon-coated lithium iron phosphate, polyvinylidene fluoride, carbon black SP, trialkyl phosphate and polyvinyl pyrrolidone, wherein the content of the trialkyl phosphate is 0.1%, and the content of the polyvinyl pyrrolidone is 0.01%.
[0085] In a specific embodiment, the positive electrode slurry includes carbon-coated lithium iron phosphate, polyvinylidene fluoride, carbon black SP, trialkyl phosphate and polyvinyl pyrrolidone, wherein the content of the trialkyl phosphate is 0.1%, and the content of the polyvinyl pyrrolidone is 0.005%.
[0086] In a specific embodiment, the positive electrode slurry includes carbon-coated lithium iron phosphate, polyvinylidene fluoride, polyacrylic acid, carbon black SP, trialkyl phosphate and polyvinyl pyrrolidone, wherein the content of trialkyl phosphate is 0.1% and the content of polyvinyl pyrrolidone is 0.05%.
[0087] In a specific embodiment, the positive electrode slurry includes carbon-coated lithium iron phosphate, Li5FeO4, polyvinylidene fluoride, carbon black SP, trialkyl phosphate and polyvinyl pyrrolidone, wherein the content of trialkyl phosphate is 0.1% and the content of polyvinyl pyrrolidone is 0.05%.
[0088] In a specific embodiment, the positive electrode slurry includes carbon-coated lithium iron phosphate, Li5FeO4, polyvinylidene fluoride, trialkyl phosphate and polyvinyl pyrrolidone, wherein the content of trialkyl phosphate is 0.1% and the content of polyvinyl pyrrolidone is 0.05%.
[0089] In some preferred embodiments, the method for preparing the positive electrode slurry comprises the following steps:
[0090] S1, performing a first mixing of the positive electrode active material, the binder and the solvent in the positive electrode slurry to obtain a first mixed material;
[0091] S2, performing a second mixing of the first mixed material and the component A to obtain a second mixed material;
[0092] S3, performing a third mixing of the second mixed material and the component B.
[0093] In some preferred embodiments, in step S1, the first mixing method is a kneading process.
[0094] In some preferred embodiments, in step S2, the second mixing method is stirring; in step S3, the third mixing method is stirring; and the stirring speed of the second mixing is greater than or equal to the stirring speed of the third mixing.
[0095] In some preferred embodiments, in step S3, the third mixing further comprises adding a solvent to adjust the viscosity.
[0096] Positive electrode
[0097] In the positive electrode sheet provided in the second aspect of the present invention, it includes a positive electrode current collector and a positive electrode material layer located on at least one surface of the positive electrode current collector, and the positive electrode material layer is formed by the positive electrode slurry as described above.
[0098] In the positive electrode sheet provided in the third aspect of the present invention, it includes a positive electrode current collector and a positive electrode material layer located on at least one surface of the positive electrode current collector, the positive electrode material layer includes a positive electrode active material, a binder and a dispersant; the dispersant includes component A and component B; the component A is an acidic dispersant; the component B is an alkaline dispersant; the mass ratio of component A to component B is (1-30): 1; the positive electrode active material includes carbon-coated lithium iron phosphate; the binder includes polyvinylidene fluoride.
[0099] In the positive electrode sheet of the third aspect, the types of the dispersant, the component A, the component B and the binder are as described above, and the content of each component is the mass percentage of the positive electrode material layer.
[0100] In a specific embodiment, the positive electrode material layer includes carbon-coated lithium iron phosphate, polyvinylidene fluoride, carbon black SP, trialkyl phosphate and polyvinyl pyrrolidone, wherein the content of trialkyl phosphate is 0.1% and the content of polyvinyl pyrrolidone is 0.05%.
[0101] In a specific embodiment, the positive electrode material layer includes carbon-coated lithium iron phosphate, polyvinylidene fluoride, carbon black SP, trialkyl phosphate and polyvinyl pyrrolidone, wherein the content of trialkyl phosphate is 0.1% and the content of polyvinyl pyrrolidone is 0.03%.
[0102] In a specific embodiment, the positive electrode material layer includes carbon-coated lithium iron phosphate, polyvinylidene fluoride, carbon black SP, carboxylic acid polyester and polyvinyl pyrrolidone, the content of the carboxylic acid polyester is 0.1%, and the content of the polyvinyl pyrrolidone is 0.05%.
[0103] In a specific embodiment, the positive electrode material layer includes carbon-coated lithium iron phosphate, polyvinylidene fluoride, carbon black SP, carboxylic acid polyester, trialkyl phosphate and polyvinyl pyrrolidone, wherein the sum of the contents of carboxylic acid polyester and trialkyl phosphate is 0.1%, and the content of polyvinyl pyrrolidone is 0.05%.
[0104] In a specific embodiment, the positive electrode material layer includes carbon-coated lithium iron phosphate, polyvinylidene fluoride, carbon black SP, polyacrylic acid and polyvinyl pyrrolidone, wherein the content of polyacrylic acid is 0.1% and the content of polyvinyl pyrrolidone is 0.05%.
[0105] In a specific embodiment, the positive electrode material layer includes carbon-coated lithium iron phosphate, polyvinylidene fluoride, carbon black SP, sorbitan monolaurate and polyvinyl pyrrolidone, wherein the content of sorbitan monolaurate is 0.1% and the content of polyvinyl pyrrolidone is 0.05%.
[0106] In a specific embodiment, the positive electrode material layer includes carbon-coated lithium iron phosphate, polyvinylidene fluoride, carbon black SP, trialkyl phosphate and benzamide, wherein the content of trialkyl phosphate is 0.1%, and the content of benzamide is 0.05%.
[0107] In a specific embodiment, the positive electrode material layer includes carbon-coated lithium iron phosphate, polyvinylidene fluoride, carbon black SP, trialkyl phosphate and benzamide, wherein the content of trialkyl phosphate is 0.12%, and the content of benzamide is 0.03%.
[0108] In a specific embodiment, the positive electrode material layer includes carbon-coated lithium iron phosphate, polyvinylidene fluoride, carbon black SP, trialkyl phosphate and hexadecyltrimethylammonium bromide, wherein the content of trialkyl phosphate is 0.1% and the content of hexadecyltrimethylammonium bromide is 0.05%.
[0109] In a specific embodiment, the positive electrode material layer includes carbon-coated lithium iron phosphate, polyvinylidene fluoride, carbon black SP, trialkyl phosphate and polyacrylonitrile, wherein the content of trialkyl phosphate is 0.1% and the content of polyacrylonitrile is 0.05%.
[0110] In a specific embodiment, the positive electrode material layer includes carbon-coated lithium iron phosphate, polyvinylidene fluoride, carbon black SP, trialkyl phosphate and polyvinyl pyrrolidone, wherein the content of trialkyl phosphate is 1% and the content of polyvinyl pyrrolidone is 0.05%.
[0111] In a specific embodiment, the positive electrode material layer includes carbon-coated lithium iron phosphate, polyvinylidene fluoride, carbon black SP, trialkyl phosphate and polyvinyl pyrrolidone, wherein the content of trialkyl phosphate is 0.05%, and the content of polyvinyl pyrrolidone is 0.05%.
[0112] In a specific embodiment, the positive electrode material layer includes carbon-coated lithium iron phosphate, polyvinylidene fluoride, carbon black SP, trialkyl phosphate and polyvinyl pyrrolidone, wherein the content of trialkyl phosphate is 0.2% and the content of polyvinyl pyrrolidone is 0.05%.
[0113] In a specific embodiment, the positive electrode material layer includes carbon-coated lithium iron phosphate, polyvinylidene fluoride, carbon black SP, trialkyl phosphate and polyvinyl pyrrolidone, wherein the content of trialkyl phosphate is 1.5%, and the content of polyvinyl pyrrolidone is 0.05%.
[0114] In a specific embodiment, the positive electrode material layer includes carbon-coated lithium iron phosphate, polyvinylidene fluoride, carbon black SP, trialkyl phosphate and polyvinyl pyrrolidone, wherein the content of trialkyl phosphate is 0.1% and the content of polyvinyl pyrrolidone is 0.01%.
[0115] In a specific embodiment, the positive electrode material layer includes carbon-coated lithium iron phosphate, polyvinylidene fluoride, carbon black SP, trialkyl phosphate and polyvinyl pyrrolidone, wherein the content of trialkyl phosphate is 0.1% and the content of polyvinyl pyrrolidone is 0.005%.
[0116] In a specific embodiment, the positive electrode material layer includes carbon-coated lithium iron phosphate, polyvinylidene fluoride, polyacrylic acid, carbon black SP, trialkyl phosphate and polyvinyl pyrrolidone, wherein the content of trialkyl phosphate is 0.1% and the content of polyvinyl pyrrolidone is 0.05%.
[0117] In the present invention, the positive electrode current collector may be a conventional positive electrode current collector in the art. The positive electrode current collector is a substrate supporting the positive electrode material layer, usually a metal foil with a thickness of 3-500 microns. There is no particular restriction on the material, as long as it has high conductivity and does not produce chemical reactions in the secondary battery system. For example, it can be a foil formed after surface treatment of nickel, titanium, aluminum, nickel, silver, stainless steel, carbon, etc. The positive electrode current collector usually has a smooth surface, but fine lines can also be formed on its surface to increase the adhesion between the positive electrode active material and the current collector. In addition to the foil, the positive electrode current collector can also be used in any one or more combinations of various forms such as film, mesh, porous, foam or non-woven fabric. Generally, the positive electrode current collector is aluminum foil.
[0118] In some embodiments, the preparation method of the positive electrode sheet includes: fully stirring and mixing the components of the positive electrode material layer in a solvent to obtain a positive electrode slurry, coating it on at least one surface of the positive electrode collector, drying it, and rolling and compacting it.
[0119] Electrochemical Devices
[0120] The electrochemical device provided in the fourth aspect of the present invention comprises the positive electrode sheet as described above.
[0121] In the present invention, the electrochemical device is preferably a battery.
[0122] In an optional embodiment, the electrochemical device is a lithium ion battery; the lithium ion battery further comprises a negative electrode sheet, a separator and an electrolyte.
[0123] Negative plate
[0124] In the present invention, the negative electrode sheet includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector.
[0125] In the present invention, the negative electrode active material in the negative electrode material layer may be a conventional negative electrode active material of a lithium ion battery in the art. The negative electrode active material of the lithium ion battery may use a compound that can reversibly embed and deintercalate lithium. Specific examples include but are not limited to: carbon materials such as crystalline carbon (natural graphite and artificial graphite, etc.), amorphous carbon, carbon-coated graphite and resin-coated graphite, or oxide materials such as indium oxide, silicon oxide, tin oxide, lithium titanate, zinc oxide, lithium oxide, etc., or lithium metal or a metal material that can form an alloy with lithium; wherein the metal material that can form an alloy with lithium is, for example, Cu, Sn, Si, Co, Mn, Fe, Sb and Ag. Binary or ternary alloys containing these metals and lithium may also be used as negative electrode active materials. These negative electrode active materials may be used alone or in combination of two or more. From the perspective of high energy density, carbon materials such as graphite may also be used in combination with Si, Si alloys, Si oxides and other Si-based materials.
[0126] In some embodiments, the negative electrode active material includes any one of soft carbon, hard carbon, artificial graphite, natural graphite, silicon, silicon oxides, silicon carbon compounds, or lithium titanate, or a combination of at least two thereof.
[0127] In one specific embodiment, the negative electrode active material is artificial graphite.
[0128] In some embodiments, the negative electrode material layer further includes a thickener.
[0129] The addition of the thickener can increase the system viscosity of each component in the negative electrode slurry, and can be a thickener conventionally used in the art for preparing negative electrode sheets, such as sodium carboxymethyl cellulose (CMC).
[0130] In some embodiments, the negative electrode material layer further includes a conductive agent.
[0131] There are no particular restrictions on the conductive agent, as long as it has conductivity and does not cause chemical changes in the battery. For example, the conductive agent may be: graphite, such as natural graphite or artificial graphite; carbon-based materials, such as carbon black (Super P), acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black or carbon fiber; metal powder or metal fiber, such as copper, nickel, aluminum or silver; conductive whiskers, such as zinc oxide whiskers or potassium titanate whiskers; conductive metal oxides, such as titanium dioxide; or conductive polymers, such as polyphenylene derivatives.
[0132] In some embodiments, the negative electrode material layer further includes a binder.
[0133] The type of the binder is not particularly limited, and can be selected from polyvinylidene fluoride, polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid (PAA), ethylene-propylene-diene terpolymer and its sulfonate, styrene-butadiene rubber (SBR), fluororubber and various copolymers.
[0134] In some specific embodiments, in the negative electrode material layer, the mass ratio of the negative electrode active material, the conductive agent, the binder and the thickener is 97.3:0.4:1.8:0.5.
[0135] In the present invention, the negative electrode current collector may be a conventional negative electrode current collector in the art. The negative electrode current collector is a substrate supporting the negative electrode active material, usually a metal foil with a thickness of 3-500 microns. There is no particular restriction on the material, as long as it has high conductivity and does not produce chemical reactions in the secondary battery system. For example, it can be a foil formed after surface treatment of nickel, titanium, aluminum, nickel, silver, stainless steel, carbon, etc. The negative electrode current collector usually has a smooth surface, but fine lines can also be formed on its surface to increase the adhesion between the positive electrode active material and the current collector. In addition to the foil, the negative electrode current collector can also be used in any one or more combinations of various forms such as film, mesh, porous, foam or non-woven fabric. Generally, the negative electrode current collector is copper foil. The thickness of the negative electrode current collector is, for example, 10μm.
[0136] In some embodiments, the method for preparing the negative electrode sheet comprises the following steps: thoroughly stirring and mixing the components of the negative electrode material layer in a solvent to obtain a negative electrode slurry which is applied on at least one surface of the negative electrode current collector, dried, cold pressed, and cut.
[0137] Diaphragm
[0138] In some optional embodiments, the separator may be a polypropylene film or a polyethylene film.
[0139] Wherein, the air permeability of the diaphragm may be 180-380 s / 100mL.
[0140] Wherein, the porosity of the diaphragm may be 30%-50%.
[0141] Wherein, the thickness of the diaphragm may be 9-18 μm.
[0142] In a specific embodiment, the diaphragm is a polyethylene film; the thickness of the diaphragm is 11 μm; the air permeability of the diaphragm is 230 s / 100 mL; and the porosity of the diaphragm is 40%.
[0143] Electrolyte
[0144] In some embodiments, the electrolyte may be an electrolyte conventionally used for batteries in the art, generally including a non-aqueous solvent, a lithium salt, and additives.
[0145] In some embodiments, the preparation method of the lithium-ion battery includes the following steps: stacking the positive electrode sheet, the separator, and the negative electrode sheet in sequence, so that the separator is located between the positive and negative electrode sheets to play an isolating role; then wrapping with an aluminum-plastic film, injecting the electrolyte after drying, and finally preparing a soft-pack battery through packaging, standing, formation and other processes.
[0146] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0147] The reagents and raw materials used in the present invention are commercially available.
[0148] The main reagents used in the following examples and comparative examples are as follows:
[0149] Polyvinylidene fluoride (PVDF) was purchased from Arkema (Changshu) Special Materials Co., Ltd., product model HSV900;
[0150] Polyacrylic acid (PAA) was purchased from Indile Technology Co., Ltd., product model LA133;
[0151] Trialkyl phosphate was purchased from Nantong Gaokai Chemical Co., Ltd., product model C1618 phosphate;
[0152] Polyvinyl pyrrolidone was purchased from Huzhou Shenhua Polymer Materials Co., Ltd., product model K90;
[0153] Polyacrylonitrile was purchased from Dongguan Hengtai Plastic Technology Co., Ltd. and was in powdered form;
[0154] Benzamide was purchased from Weifang Qianjin Fine Chemical Co., Ltd., product model 55-21-0;
[0155] Hexadecyltrimethylammonium bromide was purchased from Shandong Poly Chemical Co., Ltd. with the product model number 57-09-0.
[0156] Example 1
[0157] (1) Preparation of positive electrode slurry
[0158] S1. First Mixing:
[0159] S1-1, adding positive electrode active material, PVDF and SP (contents of 97.35%, 1.8% and 0.7% respectively) into a stirring device for pre-dispersion treatment at a speed of 800 rpm for 30 minutes to obtain a premix; wherein the positive electrode active material is carbon-coated LFP (carbon coating amount is 1.3%);
[0160] S1-2, adding solvent NMP to the premix and kneading the premix at a rotation speed of 500 rpm for 30 min to obtain a first mixture;
[0161] S2, second mixing: adding trialkyl phosphate (content of 0.1%) to the first mixed material, and performing high-speed dispersion treatment at a speed of 3000 rpm for 60 min to obtain a second mixed material;
[0162] S3, third mixing: PVP (content of 0.05%) is added to the second mixed material, and a high-speed dispersion treatment is carried out at a rotation speed of 3000 rpm for 180 min. After the dispersion treatment, appropriate amount of NMP is added to adjust the viscosity to 4000-10000 mPa·s.
[0163] (2) Preparation of positive electrode
[0164] The obtained positive electrode slurry is coated on at least one surface of the positive electrode current collector, dried, and rolled to obtain the positive electrode slurry.
[0165] Example 2
[0166] The difference between Example 2 and Example 1 is that in the process of preparing the positive electrode slurry, component A in step S2 uses carboxylic acid polyester and trialkyl phosphate (mass ratio is 1:1, and the content of component A is still 0.1%). The other conditions are the same as in Example 1.
[0167] Example 3
[0168] The difference between Example 3 and Example 1 is that in the process of preparing the positive electrode slurry, carboxylic acid polyester is used instead of trialkyl phosphate in step S2. The other conditions are the same as those in Example 1.
[0169] Example 4
[0170] The difference between Example 4 and Example 1 is that in the process of preparing the positive electrode slurry, polyacrylic acid is used instead of trialkyl phosphate in step S2. The other conditions are the same as those in Example 1.
[0171] Example 5
[0172] The difference between Example 5 and Example 1 is that in the process of preparing the positive electrode slurry, sorbitan monolaurate is used instead of trialkyl phosphate in step S2. The other conditions are the same as those in Example 1.
[0173] Example 6
[0174] The difference between Example 6 and Example 1 is that in the process of preparing the positive electrode slurry, benzamide is used instead of PVP in step S3. The other conditions are the same as those in Example 1.
[0175] Example 7
[0176] The difference between Example 7 and Example 6 is that in the process of preparing the positive electrode slurry, the content of trialkyl phosphate in step S2 is 0.12%, and the content of benzamide in step S3 is 0.03%. The other conditions are the same as those in Example 6.
[0177] Example 8
[0178] The difference between Example 8 and Example 1 is that in the process of preparing the positive electrode slurry, CTAB is used instead of PVP in step S3. The other conditions are the same as those in Example 1.
[0179] Example 9
[0180] The difference between Example 9 and Example 1 is that in the process of preparing the positive electrode slurry, polyacrylonitrile is used instead of PVP in step S3. The other conditions are the same as those in Example 1.
[0181] Example 10
[0182] The difference between Example 10 and Example 1 is that in the process of preparing the positive electrode slurry, the content of the carbon-coated LFP in step S1-1 is 96.45%, and the content of the trialkyl phosphate in step S2 is 1%. The other conditions are the same as those in Example 1.
[0183] Embodiment 11
[0184] The difference between Example 11 and Example 1 is that in the process of preparing the positive electrode slurry, the content of the carbon-coated LFP in step S1-1 is 97.4%, and the content of the trialkyl phosphate in step S2 is 0.05%. The other conditions are the same as those in Example 1.
[0185] Example 12
[0186] The difference between Example 12 and Example 1 is that in the process of preparing the positive electrode slurry, the content of the carbon-coated LFP in step S1-1 is 97.25%, and the content of the trialkyl phosphate in step S2 is 0.2%. The other conditions are the same as those in Example 1.
[0187] Embodiment 13
[0188] The difference between Example 13 and Example 1 is that in the process of preparing the positive electrode slurry, the content of the carbon-coated LFP in step S1-1 is 95.95%, and the content of the trialkyl phosphate in step S2 is 1.5%. The other conditions are the same as those in Example 1.
[0189] Embodiment 14
[0190] The difference between Example 14 and Example 1 is that in the process of preparing the positive electrode slurry, the content of the carbon-coated LFP in step S1-1 is 97.37%, and the content of PVP in step S3 is 0.03%. The other conditions are the same as those in Example 1.
[0191] Embodiment 15
[0192] The difference between Example 15 and Example 1 is that in the process of preparing the positive electrode slurry, the content of the carbon-coated LFP in step S1-1 is 97.39%, and the content of PVP in step S3 is 0.01%. The other conditions are the same as those in Example 1.
[0193] Example 16
[0194] The difference between Example 16 and Example 1 is that in the process of preparing the positive electrode slurry, the content of the carbon-coated LFP in step S1-1 is 97.395%, and the content of PVP in step S3 is 0.005%. The other conditions are the same as those in Example 1.
[0195] Embodiment 17
[0196] The difference between Example 17 and Example 1 is that in the process of preparing the positive electrode slurry, the carbon coating amount of the carbon-coated LFP in step S1-1 is 0.7%. The other conditions are the same as those in Example 1.
[0197] Embodiment 18
[0198] The difference between Example 18 and Example 1 is that in the process of preparing the positive electrode slurry, the binder in step S1-1 is PVDF and PAA (mass ratio is 1:1, and the content of the binder is still 1.8%). The other conditions are the same as in Example 1.
[0199] Embodiment 19
[0200] The difference between Example 19 and Example 1 is that in the process of preparing the positive electrode slurry, the conductive agent SP is not used in step S1-1 (the contents of the positive electrode active material and PVDF are 98.05% and 1.8%, respectively), and the other conditions are consistent with Example 1.
[0201] Embodiment 20
[0202] The difference between Example 20 and Example 1 is that in the process of preparing the positive electrode slurry, the carbon coating amount of the carbon-coated LFP in step S1-1 is 0.05%. The other conditions are the same as those in Example 1.
[0203] Embodiment 21
[0204] The difference between Example 21 and Example 1 is that in the process of preparing the positive electrode slurry, the carbon coating amount of the carbon-coated LFP in step S1-1 is 5%. The other conditions are the same as those in Example 1.
[0205] Comparative Example 1
[0206] (1) Preparation of positive electrode slurry
[0207] S1. First Mixing:
[0208] The content of carbon-coated LFP in S1-1 was 97.3%, and the other conditions were the same as those in Example 1;
[0209] S1-2 is the same as in Example 1;
[0210] S2, second mixing: add trialkyl phosphate (content of 0.2%) to the first mixed material, and perform high-speed dispersion treatment at a rotation speed of 3000 rpm for 240 min. After the dispersion treatment, add appropriate amount of NMP to adjust the viscosity to mPa·s.
[0211] (2) The preparation of the positive electrode is consistent with that in Example 1.
[0212] Comparative Example 2
[0213] (1) Preparation of positive electrode slurry
[0214] S1. First Mixing:
[0215] The content of carbon-coated LFP in S1-1 was 97.42%, and the other conditions were the same as in Example 1;
[0216] S1-2 is the same as in Example 1;
[0217] S2, second mixing: PVP (content of 0.08%) is added to the first mixture, and a high-speed dispersion treatment is carried out at a rotation speed of 3000 rpm for 240 min. After the dispersion treatment, appropriate amount of NMP is added to adjust the viscosity to 4000-10000 mPa·s.
[0218] (2) The preparation of the positive electrode is consistent with that in Example 1.
[0219] Comparative Example 3
[0220] The difference between Comparative Example 3 and Example 1 is that in the process of preparing the positive electrode slurry, trialkyl phosphate is used instead of PVP in step S3. The other conditions are the same as those in Example 1.
[0221] Comparative Example 4
[0222] The difference between Comparative Example 4 and Example 1 is that in the process of preparing the positive electrode slurry, PVP is used instead of trialkyl phosphate in step S2. The other conditions are the same as those in Example 1.
[0223] Comparative Example 5
[0224] The difference between Comparative Example 5 and Example 1 is that in the process of preparing the positive electrode slurry, the content of the carbon-coated LFP in step S1-1 is 97.44%, and the content of the trialkyl phosphate in step S2 is 0.01%. The other conditions are the same as those in Example 1.
[0225] Comparative Example 6
[0226] The difference between Comparative Example 6 and Example 1 is that in the process of preparing the positive electrode slurry, the content of the carbon-coated LFP in step S1-1 is 97.445%, and the content of the trialkyl phosphate in step S2 is 0.005%. The other conditions are the same as those in Example 1.
[0227] Comparative Example 7
[0228] The difference between Comparative Example 7 and Example 1 is that in the process of preparing the positive electrode slurry, the content of the carbon-coated LFP in step S1-1 is 97.25%, and the content of PVP in step S3 is 0.15%. The other conditions are the same as those in Example 1.
[0229] Comparative Example 8
[0230] The difference between Comparative Example 8 and Example 19 is that in the process of preparing the positive electrode slurry, trialkyl phosphate is used instead of PVP in step S3, and the other conditions are consistent with Example 19.
[0231] Comparative Example 9
[0232] The difference between Comparative Example 9 and Example 19 is that in the process of preparing the positive electrode slurry, PVP is used instead of trialkyl phosphate in step S2, and the other conditions are consistent with Example 19.
[0233] Comparative Example 10
[0234] The difference between Comparative Example 10 and Example 1 is that during the preparation of the positive electrode slurry, the carbon-coated LFP in step S1-1 is replaced by NCM811 (Li(Ni 0.8 Co 0.1 Mn 0.1)O2), and no conductive agent SP is used (the contents of positive electrode active material and PVDF are 98.05% and 1.8% respectively), trialkyl phosphate is used instead of PVP in step S3, and the other conditions are consistent with Example 1.
[0235] Comparative Example 11
[0236] The difference between Comparative Example 11 and Example 1 is that during the preparation of the positive electrode slurry, the carbon-coated LFP in step S1-1 is replaced by NCM811 (Li(Ni 0.8 Co 0.1 Mn 0.1 )O2), and no conductive agent SP is used (the contents of positive electrode active material and PVDF are 98.05% and 1.8% respectively), PVP is used instead of trialkyl phosphate in step S2, and the other conditions are consistent with Example 1.
[0237] Comparative Example 12
[0238] The difference between Comparative Example 12 and Example 1 is that during the preparation of the positive electrode slurry, the carbon-coated LFP in step S1-1 is replaced by NCM811 (Li(Ni 0.8 Co 0.1 Mn 0.1 )O2), and no conductive agent SP is used (the contents of the positive electrode active material and PVDF are 98.05% and 1.8% respectively), and the other conditions are consistent with Example 1.
[0239] Comparative Example 13
[0240] The difference between Comparative Example 13 and Example 1 is that during the preparation of the positive electrode slurry, the carbon-coated LFP in step S1-1 is replaced by NCM811 containing CNT (the amount of CNT added is 0.3%), and the conductive agent SP is not used (the contents of the positive electrode active material and PVDF are 98.05% and 1.8%, respectively), and the other conditions remain the same as in Example 1.
[0241] Comparative Example 14
[0242] The difference between Comparative Example 14 and Example 1 is that during the preparation of the positive electrode slurry, the carbon-coated LFP in step S1-1 is replaced by NCM811 containing CNTs (the amount of CNT added is 0.3%, which is the mass percentage of CNTs to the mass percentage of NCM811), and the other conditions remain the same as in Example 1.
[0243] Comparative Example 15
[0244] The difference between Comparative Example 15 and Example 1 is that in the process of preparing the positive electrode slurry, the carbon-coated LFP in step S1-1 is replaced with carbon-coated NCM811 (the carbon coating amount is 0.3%, NCM811 contains CNT, and the addition amount of CNT is 0.3%). The other conditions are the same as those in Example 1.
[0245] Comparative Example 16
[0246] The difference between Comparative Example 16 and Example 1 is that in the process of preparing the positive electrode slurry, the carbon-coated LFP in step S1-1 is replaced with carbon-coated NCM811 (the carbon coating amount is 0.3%, and NCM811 does not contain CNT). The other conditions are the same as those in Example 1.
[0247] Effect Example 1
[0248] The positive electrode slurries prepared in Examples 1-21 and Comparative Examples 1-16 were tested for pH value, viscosity, solid content and coating speed as follows:
[0249] (1) pH value of cathode slurry
[0250] The pH value of the positive electrode slurry was tested using a pH meter (manufacturer: Mettler Toledo Technologies (China) Co., Ltd., model: S-400K). The test results are shown in Table 1-3.
[0251] (2) Viscosity of positive electrode slurry
[0252] The viscosity test was conducted using a viscosity tester (manufacturer: AMETEK Brookfield, model: DV2T). The test results are shown in Tables 1-3 and Figure 1 shown.
[0253] (3) Solid content of positive electrode slurry
[0254] The solid content was tested using a solid content detector (manufacturer: Xiamen Lesde Scientific Instrument Co., Ltd., model: QL-720D). The test results are shown in Table 1-3.
[0255] (4) Coating speed of positive electrode slurry
[0256] The coating speed is the maximum coating speed on the coating machine that ensures the film surface is intact at a temperature of 95°C, a wind frequency of 15Hz, and a coating surface density of 24.67mg / cm². The test results are shown in Table 1-3.
[0257] Effect Example 2
[0258] The positive electrode sheets prepared in Examples 1-21 and Comparative Examples 1-16 were tested for peeling force, and the specific test conditions were as follows:
[0259] The peel force was tested using a peel force tester (universal material testing machine, Instron 5940);
[0260] Cut the electrode to be tested into long strips (length × width = 10 cm × 3 cm), and glue it to a long quartz glass plate with VHB tape (the area is slightly larger than the electrode). Use a special small round roller to repeatedly roll the electrode three times to ensure that the electrode and VHB are fully bonded. Select the standard method of measuring the peeling force at 180° to test the peeling force of the electrode. Test each sample three times and take the average value. The test results are shown in Table 1-3.
[0261] Effect Example 3
[0262] A lithium ion battery is prepared using the positive electrode sheets prepared in Examples 1-21 and Comparative Examples 1-16. The preparation method of the lithium ion battery comprises the following steps:
[0263] The positive electrode sheet, the negative electrode sheet and the separator are wound to obtain a battery cell, which is then packaged in a packaging shell and injected with electrolyte.
[0264] Among them, the preparation of the negative electrode sheet includes the following steps: mixing the negative electrode active material (artificial graphite), conductive agent (SP), binder (PAA and SBR, the mass ratio of the two is 1.3:0.5) and thickener carboxymethyl cellulose (CMC) in a mass ratio of 97.3:0.4:1.8:0.5 (a total of 100 parts by mass), adding 82 parts by mass of deionized water and mixing evenly to obtain a negative electrode slurry; then the negative electrode slurry is evenly coated on the negative electrode collector (copper foil with a thickness of 10 μm); and then after drying, rolling, cutting and other processes, the negative electrode sheet is prepared.
[0265] Among them, the diaphragm is a polyethylene film; the thickness of the diaphragm is 11 μm; the air permeability of the diaphragm is 230 s / 100 mL; and the porosity of the diaphragm is 40%.
[0266] Among them, the electrolyte used is commercial electrolyte (the manufacturer is Xinya Shanshan New Materials Technology (Quzhou) Co., Ltd., model E3).
[0267] The capacity retention rate of the lithium-ion battery prepared above was tested, and the test steps were as follows:
[0268] At 25°C, after 3 cycles of activation at 0.33C charge and discharge, charge to 80% SOC at 1C, charge 80%-100% SOC (3.65V) at 0.33C, and discharge to 2.5V at 1C; the capacity of the first cycle using this process is C0, and the capacity after 500 cycles using this process is C1; the capacity retention rate is C1 / C0×100%. The test results are shown in Table 1-3.
[0269]
[0270]
[0271]
[0272] Note: “ / ” in Table 2-3 means that the condition parameter is not involved in the specific experiment.
[0273] In the positive electrode slurry of Examples 1-21 of the present invention, carbon-coated LFP is used as the positive electrode active material, and is matched with the composite dispersant of the present invention. Within the scope of the present invention, whether the amount of component A or component B is changed, or the type of component A or component B is changed, or the carbon coating amount is changed, or the type of binder in the positive electrode slurry is changed, the obtained positive electrode slurry has excellent coating performance, which is conducive to coating during the preparation process, and has good bonding performance. The positive electrode sheet obtained by the positive electrode slurry has a high peeling force, and the capacity retention rate of the obtained electrochemical device (especially lithium ion battery) is excellent.
[0274] Component A (acidic dispersant) has an anchoring effect on the positive electrode active material. The dispersing effect relies on the steric hindrance caused by the solvated chain segment dissolving in the solvent, inhibiting particle agglomeration and producing a dispersing effect; component B (alkaline dispersant) is anchored with the coated carbon to increase the anchoring ability of the dispersant. At the same time, the amount of component B is controlled to minimize the effect of the alkaline dispersant on the binder. Among them, according to Example 1 and Examples 3-5, it can be seen that under the same other conditions, the use of trialkyl phosphate as the acidic dispersant has better slurry coating speed and pole piece peeling force. This may be because the phosphate group in the phosphate dispersant is complexed with the surface of lithium iron phosphate to form a complex functional group, making the anchoring effect stronger.
[0275] Comparative Examples 1-4 are cases where a single component dispersant is used. Among them, in Comparative Example 1, only trialkyl phosphate (component A) is added to the first mixture for the second mixing, and the third mixing using PVP (component B) is not performed. The coating speed of the positive electrode slurry is greatly reduced, and the coating performance is deteriorated. In Comparative Example 2, only PVP (component B) is added to the first mixture for the second mixing, and the third mixing using trialkyl phosphate (component A) is not performed. The coating speed of the positive electrode slurry is greatly reduced, and the coating performance is deteriorated. Moreover, as Figure 1As shown, compared with Comparative Examples 1-2, the positive electrode slurry in Example 1 has a lower viscosity, and as the standing time increases, the viscosity can still be maintained at a low level, and the stabilizing effect is good. In Comparative Example 3, the second and third mixing were performed, but trialkyl phosphate was added in steps S2 and S3. Compared with Example 1, although the peeling force of the obtained positive electrode sheet was improved, the coating speed of the positive electrode slurry was greatly reduced, and the coating performance deteriorated. In Comparative Example 4, the second and third mixing were performed, but PVP was added in steps S2 and S3. Compared with Example 1, the coating performance of the obtained positive electrode slurry was significantly deteriorated, and the bonding performance of the positive electrode slurry was too poor, and even large-area cracking occurred, and it was impossible to coat, obtain the electrode sheet, and even the peeling force test could not be performed.
[0276] It can be seen that the dispersion effect of pure acidic dispersants on lithium iron phosphate is limited, and the effect of reducing viscosity and stabilizing viscosity is general. The use of pure alkaline dispersants makes the alkalinity of the positive electrode slurry stronger, and PVDF is more likely to undergo gelation and irreversible alkaline hydrolysis, resulting in the breakage of polymer chains and destruction of the structure, thus failing to ensure the bonding performance of the positive electrode slurry.
[0277] In Comparative Examples 5 and 6, the content of component A (acidic dispersant) in the second mixing of step S2 is relatively too low, and the coating speed of the slurry is worse than that of Example 1. In Comparative Example 7, the amount of component B (alkaline dispersant) in the third mixing of step S3 is relatively too high, and the coating speed of the slurry is worse than that of Example 1.
[0278] When the positive electrode slurry does not use a conductive agent, the composite dispersant of the present invention is also superior to a single dispersant component in terms of coating performance and bonding performance. In Comparative Example 8, when the positive electrode slurry does not use a conductive agent and the dispersant uses only a single component A, compared with Example 19, although the peeling force of the positive electrode sheet is improved, the coating speed of the positive electrode slurry is significantly reduced, which is not conducive to coating during the preparation process. In Comparative Example 9, when the positive electrode slurry does not use a conductive agent and the dispersant uses only a single component B, compared with Example 19, the coating speed of the positive electrode slurry and the peeling force of the positive electrode sheet are greatly reduced.
[0279] Comparative Examples 10-16 are cases where NCM is used as the positive electrode active material. In Comparative Examples 12-13, the positive electrode active material is NCM811 without CNT or containing CNT, and no conductive agent is used. Although the coating speed of the positive electrode slurry is increased compared to when only trialkyl phosphate is used in Comparative Example 10 or only PVP is used in Comparative Example 11, the coating performance of the obtained positive electrode slurry is improved; however, compared with the carbon-coated lithium iron phosphate used as the positive electrode active material in Example 19, the coating performance of the obtained positive electrode slurry is also significantly poor. In Comparative Example 14, the positive electrode slurry contains a conductive agent, and NCM811 containing CNT is used as the positive electrode active material. Compared with the carbon-coated lithium iron phosphate used as the positive electrode active material in Example 1, the coating speed of the obtained positive electrode slurry is significantly reduced, and the coating performance is poor. In Comparative Examples 15-16, the positive electrode slurry contains a conductive agent, and carbon-coated NCM811 containing CNTs and carbon-coated NCM811 without CNTs are used as positive electrode active materials, respectively. Although two dispersants are used, the coating speed of the obtained positive electrode slurry is significantly reduced and the coating performance is poor compared with the carbon-coated lithium iron phosphate used as the positive electrode active material in Example 1. It can be seen that the composite dispersant of the present invention is used in combination with the carbon-coated lithium iron phosphate positive electrode active material to simultaneously take into account excellent coating performance and bonding performance.
[0280] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.
Claims
1. A positive electrode slurry, characterized in that: It includes a positive electrode active material, a binder and a dispersant; wherein the dispersant includes component A and component B; component A is an acidic dispersant; component B is an alkaline dispersant; the mass ratio of component A to component B is (1-30):1; the positive electrode active material includes carbon-coated lithium iron phosphate; the binder includes polyvinylidene fluoride; and the acidic dispersant includes trialkyl phosphate.
2. The positive electrode slurry according to claim 1, characterized in that The dispersant satisfies one or more of the following conditions be: b. Component B includes one or more of polyethyleneimine, triethanolamine, tripropanolamine, polyetheramine, polyetheramine methyl ether, hexadecyltrimethylammonium bromide, pyrrole, polypyrrole, 4-pyrrolidone, indole, polyvinylpyrrolidone, benzamide, polyacrylonitrile, polycyanate and cyano-tert-butyloxypropyltrimethoxysilane; c. The content of component A is 0.01%-1%, and the percentage is the percentage of the mass of component A to the total mass of the components in the positive electrode slurry excluding the solvent; d. The content of the component B is 0.01%-1%, and the percentage is the percentage of the mass of the component B to the total mass of the components in the positive electrode slurry excluding the solvent; e. The content of the dispersant is 0.03%-2%, and the percentage is the percentage of the mass of the dispersant to the total mass of the components in the positive electrode slurry excluding the solvent.
3. The positive electrode slurry according to claim 1, characterized in that The positive electrode slurry satisfies one or more of the following conditions af: a. The carbon coating amount in the carbon-coated lithium iron phosphate is 0.05%-5%, where the percentage is the mass percentage of carbon to the mass percentage of the carbon-coated lithium iron phosphate; b. The content of the positive electrode active material is 85%-98%, where the percentage is the mass of the positive electrode active material to the total mass of the components in the positive electrode slurry excluding the solvent; c. The content of the binder is 1%-10%, where the percentage is the mass of the binder to the total mass of the components in the positive electrode slurry excluding the solvent; d. The binder further comprises one or more of polytetrafluoroethylene, hexafluoropropylene, polyacrylonitrile, polyimide, perfluorosulfonic acid ionomer, sodium carboxymethyl cellulose, polyolefin, polyacrylic acid and polymethyl methacrylate; e. The positive electrode slurry further includes a conductive agent; the content of the conductive agent is 0.2%-3%, and the percentage is the percentage of the mass of the conductive agent to the total mass of the components in the positive electrode slurry excluding the solvent; f. The positive electrode slurry further includes a solvent; the solvent includes one or more of N-methylpyrrolidone, dimethyl carbonate, ethylene carbonate and diethylene carbonate.
4. The positive electrode slurry according to claim 1, characterized in that It satisfies one or more of the following conditions ac: a. The solid content of the positive electrode slurry is 45%-80%; b. The viscosity of the positive electrode slurry is 3000-20000 mPa·s; c. The pH value of the positive electrode slurry is 4-10.
5. The positive electrode slurry according to claim 1, characterized in that The method for preparing the positive electrode slurry comprises the following steps: S1, performing a first mixing of the positive electrode active material, the binder and the solvent in the positive electrode slurry to obtain a first mixed material; S2, performing a second mixing of the first mixed material and the component A to obtain a second mixed material; S3, performing a third mixing of the second mixed material and the component B.
6. The positive electrode slurry according to claim 5, characterized in that The method for preparing the positive electrode slurry satisfies one or more of the following conditions ae: a. In step S1, the first mixing method is kneading treatment; b. In step S2, the second mixing method is stirring; in step S3, the third mixing method is stirring; the stirring speed of the second mixing is greater than or equal to the stirring speed of the third mixing; c. In step S3, the third mixing further includes adding a solvent to adjust the viscosity; d. The second mixing time is shorter than the third mixing time; e. Before the first mixing, the positive electrode active material and the binder in the positive electrode slurry are pre-mixed, and the pre-mixing method is stirring.
7. A positive electrode sheet comprising a positive electrode current collector and a positive electrode material layer located on at least one surface of the positive electrode current collector, characterized in that: The positive electrode material layer is formed by the positive electrode slurry according to any one of claims 1 to 6.
8. A positive electrode sheet comprising a positive electrode current collector and a positive electrode material layer located on at least one surface of the positive electrode current collector, characterized in that: The positive electrode material layer includes a positive electrode active material, a binder and a dispersant; the dispersant includes component A and component B; component A is an acidic dispersant; component B is an alkaline dispersant; the mass ratio of component A to component B is (1-30):1; the positive electrode active material includes carbon-coated lithium iron phosphate; the binder includes polyvinylidene fluoride; the acidic dispersant includes trialkyl phosphate.
9. The positive electrode sheet according to claim 8, characterized in that: The dispersant satisfies one or two of the following conditions ab: a. The content of component A is 0.01%-1%, and the percentage is the percentage of the mass of component A to the total mass of the positive electrode material layer; b. The content of the component B is 0.01%-1%, and the percentage is the percentage of the mass of the component B to the total mass of the positive electrode material layer.
10. An electrochemical device, characterized in that: It comprises the positive electrode sheet as described in any one of claims 7 to 9.
Citation Information
Patent Citations
Positive mix paste for lithium secondary battery
CN102106023A
Positive electrode material, positive electrode slurry, positive electrode plate, secondary battery and electric device
CN115810728A